1993
DOI: 10.1113/jphysiol.1993.sp019881
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological effects of tachykinins and capsaicin on guinea‐pig bronchial parasympathetic ganglion neurones.

Abstract: SUMMARY1. We evaluated the effects of neurokinins, tachykinin analogues, or capsaicin on passive membrane properties of guinea-pig bronchial parasympathetic neurones using intracellular recording techniques.2. Substance P (SP) and the tachykinin analogue, acetyl-[Arg',Sar9Met(02)11]-SP(6-1 1) (ASMSP ), at concentrations selective for the neurokinin (NK)-1 receptor subtype, depolarized the resting potential (3 and 5 mV, respectively) with no change in input resistance. Neurokinin A and 8Ala8INKA(4-10), at conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 35 publications
6
80
0
Order By: Relevance
“…This suggests that, in the current in vivo model, HCl-induced sensory nerve stimulation may act on intermediate neurons and parasympathetic neurons where NK 3 receptors play a predominant role [18,19].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…This suggests that, in the current in vivo model, HCl-induced sensory nerve stimulation may act on intermediate neurons and parasympathetic neurons where NK 3 receptors play a predominant role [18,19].…”
Section: Discussionmentioning
confidence: 79%
“…Nerve pathways communicating between the oesophagus and airway may also be in the periphery, via autonomic ganglia [18,19]. Anatomical studies have demonstrated the presence of axon collaterals from visceral afferent fibres (gastro-intestinal tract, bladder, airways) in autonomic ganglia [19, 24, 25,].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, contraction of the small-and medium-sized human bronchi can also be mediated by tachykinin NK 1 receptors [10,11]. Studies on guinea pig and human airways show that NK 3 receptors facilitate cholinergic neurotransmission [12][13][14][15]. Therefore, agents blocking all three receptors may be useful in the treatment of asthma.…”
Section: Introductionmentioning
confidence: 99%